Optimization of microarray technology-based expression profiling for investigation of different animal models of pulmonary hypertension - Prakash, Jai; Justus Liebig University Giessen (My University, 2005)
Differential gene expression can be investigated effectively by microarrays. Therefore, the respective technical steps and parameters, in particular RNA extraction, cDNA labelling, hybridization and washing for low-fluorescence background on slides have to be optimized. Comparing different RNA extraction techniques, we found that TrifastTM method followed by column purification combined with DNase digestion resulted in highest RNA quality of the samples.

Mikroarrays erlauben eine effektive Untersuchung differenzieller Genexpression. Zunächst müssen hierzu jedoch die entsprechenden technischen Schritte und Parameter, insbesondere die RNA Extraktion, die Markierung der cDNA, die Hybridisierung sowie Waschschritte zur Minimierung des Hintergrunds auf den Objektträgern optimiert werden. Beim Vergleich verschiedener RNA Extraktionsprotokolle fanden wir, dass die TrifastTM Methode mit anschließender Silicasäulenaufreinigung und kombiniertem DNase Verdau die höchste RNA Qualität ergab.
Optimierung der auf Microarray-Technik basierenden Erfassung der
Keywords: optimization; microarray technology; ddc:610